Broadband tuning in a passively Q-switched erbium doped fiber laser (EDFL) via multiwall carbon nanotubes/polyvinyl alcohol (MWCNT/PVA) saturable absorber - Ahmad, Harith; Hassan, S.N.M.; Ahmad, F.; Zulkifli, M.Z.; Harun, Sulaiman Wadi (Elsevier, 2016)
An MWCNT/PVA-based Q-switched erbium-doped fiber laser (EDFL) that uses a tunable bandpass filter (TBPF) as the wavelength tuning and filtering mechanism to achieve a broadband tuning range is proposed and demonstrated. The tuning range of the generated Q-switched pulses covered a wide wavelength range of 50 nm, which spanned from 1519 nm to 1569 nm and corresponded to the S- and C-band regions. In addition, the lasing and Q-switching operations had low thresholds of 8.9 mW and 22.4 mW respectively. The highest pulse energy of 52.13 nJ was obtained at an output wavelength of 1569 nm, with a corresponding repetition rate of 26.53 kHz and pulse width of 6.10 µs, at the maximum power of 114.8 mW.